2020
DOI: 10.1002/jcla.23288
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a de novo tetrasomy 15q24.3‐25.3: Case report and literature review

Abstract: Background Terminal duplication on chromosome 15q is a rare chromosomal variation. Affected individuals show similar features such as growth dysplasia or the development of frontal bossing, body deformities, facial abnormalities, and genitourinary or cardiovascular disorders. However, it is not yet clear whether such 15q repeats lead to identifiable patterns of clinical abnormalities. Therefore, the purpose of this study was to analyze the prenatal diagnostic results and clinical manifestations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The features described in individual cases are sometimes opposing, such as overgrowth and growth restriction. 41 - 44 Given the aforementioned range of abnormalities, it is not surprising that a number of morbid genes are present at 15q25.1, with an associated broad array of functions and disease correlates. 41 Copy number losses involving the proximal region of 6q are also rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features described in individual cases are sometimes opposing, such as overgrowth and growth restriction. 41 - 44 Given the aforementioned range of abnormalities, it is not surprising that a number of morbid genes are present at 15q25.1, with an associated broad array of functions and disease correlates. 41 Copy number losses involving the proximal region of 6q are also rare.…”
Section: Discussionmentioning
confidence: 99%
“… 41 - 44 Given the aforementioned range of abnormalities, it is not surprising that a number of morbid genes are present at 15q25.1, with an associated broad array of functions and disease correlates. 41 Copy number losses involving the proximal region of 6q are also rare. A review of 12 cases by Hopkin et al 45 found that deletions involving 6q11 - 6q16 are commonly associated with hernias, upslanting palpebral fissures, and thin lips.…”
Section: Discussionmentioning
confidence: 99%
“…The features of chromosome 15q11-q13 duplication syndrome (OMIM 608636), which has been implicated in Angelman syndrome and Prader-Willi syndrome, include autism, mental retardation, ataxia, seizures, developmental delays, and behavioral problem. Many investigators have also reported several patients carrying duplication of the distal long arm in chromosome 15 [29][30][31], which manifests primarily as frontal bossing, short palpebral fissures, long philtrum, lowset ears, high-arched palate, retrognathia, arachnodactyly, microcephaly, joint contractures, and development delay. However, patients with duplication in the medial long arm of chr 15 are rare [32][33][34].…”
Section: Discussionmentioning
confidence: 99%